As mudanças nos sistemas de produção e de saberes na agricultura familiar na comunidade Santo Antônio localizada no km 115 Norte - BORGES, Rosileide Alves (2021)
The article / essay that we present here is constituted and gained body from the relationship between a set of field research and elements of analysis that emerged during the lectures and theoretical debates carried out in the classroom, along the path or trajectory of academic formation. The part of the research was carried out with peasant families who have lived, on average, for about 30 or even 40 years in the locality and work in the neighborhood of km 115 Norte, in the Santo Antônio community, approximately twenty km from the Transamazônica highway, in the municipality of Medicilândia , located between the municipalities of Altamira and Uruará, state of Pará. This theme was gaining more evident contours from a reflection on the data collected from the interviewees whose initial objective was the organization of the reports of the times communities with the purpose of interpreting , objectively, the emergence of the community, its organization, the productive and reproductive activities of the families in this resident, among many others that concern the world of peasant life and work. He was interested to know about the factors that influenced the coming of these peasant families to this region, notably to that community, about the changes in family farming that they followed in the course of their family trajectories, considering the time and conditions of their arrival until the current days, as well as the transformations in the universe of techniques and practices used by peasant families in order to guarantee their production and social reproduction in the place, and, therefore, how this knowledge linked to family farming needs to be res-signified with each change in production systems.